Feminist voices in spirituality - Hégy, Pierre (Studies in women and religion, 1996)
This work presents biographies of three outstanding contemporary women, Maisie Ward, Evelyn Underhill, and Mollie Rogers. It offers an overview of the paradigmatic changes in spirituality from obedience to healing. Finally, four chapters develop feminist metaphors. - Contents: Introduction (Patricia Wittberg); Metaphorical Shift - From chivalrous obedience to soulful healing (Pierre Hegy); God's Vulnerability and Incomprehensibility - Imagine God as a woman growing older (Sonya A. Quitslund); Women and Their Mothers - Rejecting and reclaiming the tradition of the saints (Marie Anne Mayeski); God Matters - The spirituality of Maisie Ward (Dana Greene); The Extraordinary Within the Ordinary - The life and message of Evelyn Underhill (Grace Adolphsen Brame); The Spirituality of Mollie Rogers (Elizabeth Carr); A Listening Heart - Religious life in a paradigm shift (Camilla Burns); Religious Life - Who Needs It? (Joan D. Chittister); Conclusion - Major spirituality themes for today (Piere Hegy)